ANALISIS PERAN CHATBOT DALAM MENINGKATKAN PELAYANAN TERHADAP KONSUMEN DI E-COMMERCE - Mayla Humaira As-syiva; Muhammad Irwan Padli Nasution (CV SWA Anugerah, 2023)
E-commerce, or electronic commerce, has drastically changed the business landscape by enabling businesses to sell products and services online. E-commerce encompasses the entire process of development, marketing, sales, delivery, payment and service, available 24 hours a day to customers, supported by the latest developments in AI (Artificial Intelligence). In the e-commerce landscape, chatbots have become irreplaceable virtual assistants for online stores, customers and business owners. In this case we will discuss the question of using chatbots, whether chatbots can answer all our questions and whether this service is useful for sellers. this research was conducted to answer questions that have been a question mark. This research uses the